Rudolph Archibald Reiss (1875–1929): in pursuit of truth, justice and law - Dimić, Ljubodrag (Sociološki pregled, 2020)
Instead of stone monuments weathered by time, as Branislav Nušić wrote in his literary-memoir work “The year of 1915” (Nušić, 1921) dedicated to the memory of his son who was killed in war, the Serbian nation, it is with the five-volume edition of Reiss’s collected texts (“About the crimes of Austro-Bulgaro-Germans in Serbia 1914–1918”, “War Reports from Serbia 1914–1918”, “About Serbia and Serbs”/ “What I saw and experienced in great days” and “Listen Serbs”) and the texts about Reiss and his oeuvre (“Visionary of the Modern Police” and “Serbs about Reiss”) that the Serbian people and Serbia once again express gratitude to this truth-loving scientist, humanist and friend. Thanks to this, readers will be able to evaluate on their own how this educated and well-versed contemporary – scientist, crime investigator, war correspondent from Serbia – whose “standing point” was quite high, could do and “see” in the era filled with crimes, as well as dynamic and dramatic processes, and how he is judged by the scientists in the decades connecting Reiss with the time we live in.
Keywords: Rudolph Archibald Reiss (1875–1929); Selected Works; 2019